If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + 9x = 5x + -7 Reorder the terms: 21 + 9x = -7 + 5x Solving 21 + 9x = -7 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 21 + 9x + -5x = -7 + 5x + -5x Combine like terms: 9x + -5x = 4x 21 + 4x = -7 + 5x + -5x Combine like terms: 5x + -5x = 0 21 + 4x = -7 + 0 21 + 4x = -7 Add '-21' to each side of the equation. 21 + -21 + 4x = -7 + -21 Combine like terms: 21 + -21 = 0 0 + 4x = -7 + -21 4x = -7 + -21 Combine like terms: -7 + -21 = -28 4x = -28 Divide each side by '4'. x = -7 Simplifying x = -7
| 5x-8-7x=12 | | a-90=371 | | -0.5[X-4]=1.5 | | (-6x^3+5x^2-8x+9)(17x^3+2x^2-4x-13)= | | In(3x-1)=1 | | x/182=4 | | (x-3)(x+3)-(x-4)(4+x)=2x | | 9j^2+12j-12=0 | | n^2=9n-8 | | -40-8v=6(8v+3)+2v | | 39/78=x/6 | | 7y-2y=2 | | log[6]4x^2-log[6]x=2 | | a/20=6 | | 9-9x=1-7x | | http://www.thelearningodyssey.com | | http://www.thelearningodyssey.com/Assess/DPT/QIEImagesStorage/HSLQ_/HSLQ_AI13C02_T_stem2_1.gif | | 8-3t=5t | | 8n-3(-7n-6)=-6+5n | | -05X-4=1.5 | | 16t^2+40t+20= | | 43+x=50 | | 2m^2+15=11m | | 18n^2+27n-5=0 | | b+34=19 | | 6(7+5x)=-6+6x | | 2(8x+8)=-4+6x | | 6*-2y=-4 | | (10x-2y)-(2x-7)= | | 46+x=58 | | 6+7xy= | | b-127=346 |